2017
DOI: 10.3126/jcmc.v7i3.23693
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing utilization of cervical cancer screening services among married women in community, Chitwan

Abstract: Cervical cancer is one of the most prevalent cancers affecting women globally. It is the fourth most common cancer in women and the seventh overall. The morbidity and mortality of cervical cancer can be highly reduced through vaccination against human papilloma virus, regular screening and timely intervention. The objective of this study was to find out the factors influencing utilization of cervical cancer screening services among married women aged 30-60 of Bharatpur Sub-Metropolitan 19, Chitwan. A community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The study conducted in Chitwan by Ranabhat and Thapa (2018) reported similar findings that 27.4% of the women had a good level of awareness, 22.9% had a fair level of awareness, and 49.7% of women had a poor level of awareness in cervical cancer. 21 The study conducted by Harsh and Tanya (2014) in Mangalore, India demonstrated contrast finding that 6% of the respondents had good awareness, 12% had satisfactory awareness, and 81.9% had poor awareness in cervical cancer. 22 A low level of awareness might be due to lack of population-based screening programs, inefficient mass media campaigns, and cultural barriers wherein women in Nepal feel shy to discuss the diseases affecting the sexual organs.…”
Section: Discussionmentioning
confidence: 96%
“…The study conducted in Chitwan by Ranabhat and Thapa (2018) reported similar findings that 27.4% of the women had a good level of awareness, 22.9% had a fair level of awareness, and 49.7% of women had a poor level of awareness in cervical cancer. 21 The study conducted by Harsh and Tanya (2014) in Mangalore, India demonstrated contrast finding that 6% of the respondents had good awareness, 12% had satisfactory awareness, and 81.9% had poor awareness in cervical cancer. 22 A low level of awareness might be due to lack of population-based screening programs, inefficient mass media campaigns, and cultural barriers wherein women in Nepal feel shy to discuss the diseases affecting the sexual organs.…”
Section: Discussionmentioning
confidence: 96%
“…13 However, another study to find out factors influencing utilization of cervical cancer screening services among married women aged 30-60 of Bharatpur, Nepal showed that 56% of women never utilized cervical cancer screening services. 14 Even though cervical cancer is the second common cancer among women in India, low knowledge level was reported among participants regarding cervical cancer and Pap smear screening. Current study revealed positive relationship between knowledge regarding cervical cancer screening and utilization of screening services.…”
Section: Discussionmentioning
confidence: 99%
“…Further, only 38.3% had undergone screening, although 36.1% held a positive attitude towards the procedure. 16 Comparing these findings, a study conducted in Nigeria showed that 23.4% of the respondents had a good knowledge of cervical cancer screening. However, the practice was considerably low, with only 17.6% having been screened, despite 84% displaying a positive attitude towards the procedure.…”
Section: Discussionmentioning
confidence: 95%
“…In a similar vein, a study of married women in Nepal demonstrated that 77.9% had undergone screening only once. 16 The timings of school and hospital operations in Nepal, which both typically begin at 10 am, may be inconvenient for teachers to practice screening, potentially contributing to a low practice rate. The primary purposes for undergoing screening were prevention, as stated by 32.8% of respondents, and the recommendation of a health worker, as stated by 22.7%.…”
Section: Discussionmentioning
confidence: 99%